2019
DOI: 10.3390/pathogens8030098
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Campylobacter jejuni and Campylobacter coli in Cattle and Sheep in Northern Spain and Changes in Antimicrobial Resistance in Two Studies 10-years Apart

Abstract: A cross-sectional survey was conducted in 2014–2016 in 301 ruminant herds to estimate C. jejuni and C. coli prevalence, and investigate their susceptibility to antimicrobials. Risk of shedding C. jejuni was higher in cattle than sheep (81.2% vs. 45.2%; ORadj = 5.22, p < 0.001), whereas risk of shedding C. coli was higher in sheep than in cattle (19.1% vs. 11.3%; ORadj = 1.71, p = 0.128). Susceptibility to six antimicrobials was determined by broth microdilution using European Committee for Antimicrobial Sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
8
18
1
Order By: Relevance
“…The 240 isolates identified belonging to the genus Campylobacter were then characterised into four species, of which 53 (22.08%) were identified as C. coli, 40 (16.66%) as C. jejuni, and 9 (3.73%) as C. fetus, whereas C. lari was not detected. Higher rates of C. coli and C. jejuni were detected than other Campylobacter species, and our findings corroborate the report of Hodges et al [69], Ocejo et al [70], Sulaiman et al [71], and Vinueza-Burgos et al [72]. In contrast, a low prevalence rate of C. fetus was detected, and this finding is also in agreement with the report of Sinulingga et al [56].…”
Section: Discussionsupporting
confidence: 93%
“…The 240 isolates identified belonging to the genus Campylobacter were then characterised into four species, of which 53 (22.08%) were identified as C. coli, 40 (16.66%) as C. jejuni, and 9 (3.73%) as C. fetus, whereas C. lari was not detected. Higher rates of C. coli and C. jejuni were detected than other Campylobacter species, and our findings corroborate the report of Hodges et al [69], Ocejo et al [70], Sulaiman et al [71], and Vinueza-Burgos et al [72]. In contrast, a low prevalence rate of C. fetus was detected, and this finding is also in agreement with the report of Sinulingga et al [56].…”
Section: Discussionsupporting
confidence: 93%
“…Elhadidy et al [30], found 49.7% resistance to tetracycline, much in accordance with the level of resistance found by Marotta et al [31], with 49.0% resistant isolates, even though this last study used the epidemiological cut-off values (ECOFFs) defined by EUCAST [32]. Considering the same resistance definition, the study carried out in Spain by Ocejo et al [33] showed that the level of resistance in Campylobacter spp., isolated from animals, was 76.5%. Tetracyclines were extensively used in Spain in animal husbandry, being 40% of all the antibiotics consumed in 2013 [34] and the high results of resistance found in our work might reflect this practice.…”
Section: Discussionsupporting
confidence: 74%
“…nalidixic acid) and fluoroquinolones (i.e. ciprofloxacin) are alarming as they are higher than those previously described in Europe for livestock [ 18 , 47 , 48 ]. On the other hand, a very low occurrence of resistance to macrolides and aminoglycosides was found, probably due to the relatively infrequent use of these antibiotics in food-producing species [ 46 ].…”
Section: Discussionmentioning
confidence: 99%